2014
DOI: 10.21101/cejph.a3975
|View full text |Cite
|
Sign up to set email alerts
|

Habits and Attitudes of First-Year Female Students at Warmia and Mazury University: a Call for Implementing Health Education Programme at Universities

Abstract: The research findings call for a specially designed pro-health programme to be implemented during the time of the studies in order to raise the female students' awareness of leading a health-conscious lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Increasing age and years as a student appear to be inversely proportionate to the amount of binge drinking, although, conversely, these factors are associated with increased drinking frequency. The current findings suggest that younger and less advanced students are more likely to engage in binge drinking, and this finding is supported by previous studies ( Podstawski et al, 2014 ; White et al, 2006 ). The difference in drinking habits between younger/less advanced students and older/more advanced students may suggest that students are socialised into a more continental drinking pattern that is characterised by frequent consumption of low to moderate levels of alcohol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Increasing age and years as a student appear to be inversely proportionate to the amount of binge drinking, although, conversely, these factors are associated with increased drinking frequency. The current findings suggest that younger and less advanced students are more likely to engage in binge drinking, and this finding is supported by previous studies ( Podstawski et al, 2014 ; White et al, 2006 ). The difference in drinking habits between younger/less advanced students and older/more advanced students may suggest that students are socialised into a more continental drinking pattern that is characterised by frequent consumption of low to moderate levels of alcohol.…”
Section: Discussionsupporting
confidence: 91%
“…The number of years spent as a student might also affect alcohol use, as norms in the student setting can enhance certain drinking habits and condone others ( Nedregård & Olsen, 2010 ). Some studies have suggested that certain aspects of alcohol use (such as hazardous alcohol use and frequency of drinking) increase with time spent as a student ( Davoren, Shiely, Byrne, & Perry, 2015 ; Nedregård & Olsen, 2014 ), while others have argued that first-year students seem to be particularly vulnerable to high alcohol intake and binge drinking ( Podstawski, Choszcz, Klimczak, Kolankowska, & Zurek, 2014 ; White, Kraus, & Swartzwelder, 2006 ). Because alcohol habits tend to vary significantly across cultures, country of birth may be associated with alcohol consumption ( Pedersen, 2015 ; Skogen, Bøe, Sivertsen, & Hysing, 2016 ).…”
mentioning
confidence: 99%
“…Data on average alcohol consumption by students in their first year of study are concerning. In the study by Podstawski et al [28], a relatively high percentage of female students (9%) admitted regular alcohol consumption every day; what is more, more than 12% of the respondents admitted at least one case of drinking until loss of consciousness in their first year. However, the preponderance of women in the same study (61%) reported drinking only occasionally during the first academic year.…”
Section: Health Prob Civil 2019 Volume 13 Issuementioning
confidence: 93%
“…Most certainly, the different results may be influenced by the factor of gender. Higher alcohol consumption is observed in men [3,28]. Also, the fact that the participants of the research were first-year students, at the beginning of their studies, could have eliminated the impact of "student life".…”
Section: Health Prob Civil 2019 Volume 13 Issuementioning
confidence: 99%
“…Similar research study was conducted in Europe by Steptoe et al (1997) who reported that among UCS from 21 European countries age-adjusted prevalence of physical exercise in the past 2 weeks averaged 73.2% among men and 68.3% among women, but varied significantly ISSN 1822-7864 (Print) ISSN 2538-7111 (Online) https://doi.org/10.33225/pec/20.78.1027 from more than 80% to less than 60% across country samples. Furthermore, several research studies conducted in Europe reported low PA levels among Romanian (Fagaras et al, 2015), Polish (Podstawski et al, 2014) and Spanish (Martinez-Lemos et al, 2012) students. Supplementary evidence suggests that many UCS do not meet the above recommendations in the process of transitioning from adolescence to adulthood (Kim & Cardinal, 2017;Sigmundova et al, 2013).…”
Section: Introductionmentioning
confidence: 98%